Josephine the hungry heart - Baker, Jean-Claude; Chase, Chris (Random House, 1993)
Josephine was the self-proclaimed Universal Mother, who gathered children from many countries, the expatriate who was erratic about the civil rights movement, and the outrageous entertainer who dared to become the first black sex symbol of this century
Keywords: Baker, Josephine <1906-1975>; Baker, Josephine -- 1906-1975; African American entertainers -- France -- Biography; Dancers -- France -- Biography; Frankreich; Biografie